Evolution of Innovation Cluster Policy in Ukraine - Shakhbazyan, K.S.; Dubinskyi, H.P.; Yegorov, I.Yu. (Наука та наукознавство, 2017)
The article deals with the main stages of evolution of the policy on creation and support of innovative clusters in Ukraine, key initiatives of the state on promotion of clusters are considered. Particular attention is paid to the formation of specific clusters and their further development in conditions of deep social and economic crisis. It is shown that innovative clusters have not yet become a widespread phenomenon in Ukraine due to a number of reasons that are analyzed in the article. The recommendations on measures of state support of innovative clusters in the context of European integration processes are developed, with the particular emphasis on the role of scientific centers. These centers could become the basis of such clusters. У статті розглянуто основні етапи еволюції політики щодо створення та підтримки інноваційних кластерів в Україні, проаналізовано основні ініціативи держави щодо стимулювання кластерів. Спеціальну увагу приділено становленню конкретних кластерів та їх подальшому розвитку в умовах глибокої соціально-економічної кризи. Показано, що інноваційні кластери ще не набули поширення в Україні внаслідок низки причин, які аналізуються у статті. Розроблено рекомендації щодо заходів з державної підтримки інноваційних кластерів у контексті євроїнтеграційних процесів, зокрема підкреслено роль наукових центрів, які можуть стати основою таких кластерів. В статье рассмотрены основные этапы эволюции политики по созданию и поддержке инновационных кластеров в Украине, проанализированы основные инициативы государства по стимулированию кластеров. Особое внимание уделено становлению конкретных кластеров и их дальнейшему развитию в условиях глубокого социальноэкономического кризиса. Показано, что инновационные кластеры еще не получили широкого распространения в Украине в результате ряда причин, которые анализируются в статье. Разработаны рекомендации по мерам государственной поддержки иновационных кластеров в контексте евроинтеграционных процессов, в частности подчеркнута роль научных центров, которые могут стать основой таких кластеров.